A practical approach for grid-connected pico-hydro systems using conventional photovoltaic inverters - Leite, V. (2018)
Pico-hydro power generation has a considerable untapped potential, able to contribute to the increased energy demand whilst ensuring a low environmental impact. The integration of these systems into microgrids is an emerging solution for the electrification of remote regions and also for selfsustainable power systems. The integration of cheap and wide spread technologies to interface small capacity hydro power systems with the grid has become essential in order to enable the exploitation of small rivers and shallows reservoirs resources among many other applications such as in water supply systems. This paper presents a design procedure to integrate pico-hydro generators into the grid using conventional and widespread photovoltaic inverters.